Unexpected low‐dose toxicity of the universal solvent DMSO. Issue 3 (10th December 2013) - Galvao, Joana; Davis, Benjamin; Tilley, Mark; Normando, Eduardo; Duchen, Michael R.; Cordeiro, M. Francesca
Abstract : Dimethyl sulfoxide (DMSO) is an important aprotic solvent that can solubilize a wide variety of otherwise poorly soluble polar and nonpolar molecules. This, coupled with its apparent low toxicity at concentrations <10%, has led to its ubiquitous use and widespread application. Here, we demonstrate that DMSO induces retinal apoptosis in vivo at low concentrations (5 μl intravitreally dosed DMSO in rat from a stock concentration of 1, 2, 4, and 8% v/v). Toxicity was confirmed in vitro in a retinal neuronal cell line, at DMSO concentrations >1% (v/v), using annexin V, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT), and AlamarBlue cell viability assays. DMSO concentrations > 10% (v/v) have recently been reported to cause cellular toxicity through plasma membrane pore formation. Here, we show the mechanism by which low concentrations (2–4% DMSO) induce caspase‐3 independent neuronal death that involves apoptosis‐inducing factor (AIF) translocation from mitochondria to the nucleus and poly‐(ADP‐ribose)‐polymerase (PARP) activation. These results highlight safety concerns of using low concentrations of DMSO as a solvent for in vivo administration and in biological assays. We recommend that methods other than DMSO are employed for solubilizing drugs but, where no alternative exists, researchers compute absolute DMSO final concentrations and include an untreated control group in addition to DMSO vehicle control to check for solvent toxicity.—Galvao, J., Davis, B., Tilley, M., Normando, E., Duchen, M. R., Cordeiro, M. F. Unexpected low‐dose toxicity of the universal solvent DMSO. FASEB J. 28, 1317–1330 (2014). www.fasebj.org